Optimasi Electrical Submersible Pump (ESP) Pada Sumur MFR-21 Berdasarkan Keadaan Sumur di Masa Depan - Abdi Suprayitno; Muhammad Fauzi Ramadhan; Rohima Sera Afifah (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2024)
When wells are produced continuously, the reservoir pressure will continue to decrease resulting in decreased production performance from the well. To optimally increase the rate of production, optimization is carried out using an Artificial Lift Electrical Submersible Pump. Based on data from the journal, "MFR-21" well had previously been installed Electrical Submersible Pump but was no longer functioning due to the condition of ESP pump not running or dead due to damage, so the author's goal is to optimize the pump and predict the condition of the well in the future until when the pump is no longer optimal by using Wiggins 3 Phase IPR and carrying out a scenario of decreasing reservoir pressure to predict the Future IPR "MFR-21" well. The results of 3 Phase Wiggins IPR curve analysis obtained a total production rate (Qt/Qmax) 6257 bfpd. Obtained a target production rate of 5005.6 bfpd it is recommended to use the ESP design with the Centrilift GC-8200 pump which has a production recommendation 4400 – 10000 bfpd with a number of stages 168, Horse Power 281 HP, and pump efficiency 69%. As well as using the Future IPR method to reduce 3 reservoir pressures, namely 1750, 1000, 500. When the reservoir pressure reaches 1000 and 500 psia the pump is no longer optimum because the target Q at reservoir pressure is not included in the pump production recommendations. So at reservoir pressure 1000 and 500 psia it is necessary to re-optimize the pump again according to the condition of well.